Isokinetic functional results of open and percutaneous Achilles tendon repair - Lazaroni, Pedro Sebastião de Oliveira; Baumfeld, Tiago Soares; Magalhães, João Murilo Brandão; Lopes, Fernando Araújo Silva; Amaral, Giovana Mendes; Baumfeld, Daniel Soares (Scientific Journal of the Foot & Ankle, 2018)
Objective: Achilles tendon (AT) ruptures are common in young athletes. Conservative treatment, open surgery and percutaneous/minimally invasive approaches are advocated by different groups around the world, and data are still conflicting. The objective of this study was to use objective and reliable measurements to compare the isokinetic functional results of patients undergoing open repair with those undergoing a percutaneous approach. Methods: This was a retrospective comparative study of 38 subjects undergoing two different approaches for the treatment of acute AT ruptures: open and percutaneous. For the functional evaluation, all patients were subjected to analysis of the calf muscle circumference of both legs, along with the following isokinetic measurements: total flexion work, peak flexion torque, total extension work and peak extension torque. The Achilles Tendon Rupture Score (ATRS) and American Orthopedic Foot and Ankle Score (AOFAS) evaluation scales were applied at the final 12-month follow-up. Results: No serious complications were observed. The mean time to return to sports was 9 months. The ​ AOFAS and ATRS values did not differ significantly between the two groups. The isokinetic variables and circumference in both groups were similar when the non-operated and operated limbs were compared. The groups also did not differ when comparing open and percutaneous approaches. Conclusion: It can be concluded that the two strategies used in this study achieved similar functional results. Level of Evidence III; Retrospective Comparative Study.